2010
DOI: 10.1680/geot.8.p.117.3277
|View full text |Cite
|
Sign up to set email alerts
|

Creep, strength and other characteristics of Hawaiian volcanic soils

Abstract: Strength, creep and other properties of four volcanic soils from Hawaii were investigated under reconstituted triaxial conditions. The selected soils are of different geological origin and have contrasting index properties. Results from triaxial tests suggest that as clayey volcanic soils weather toward a siltier texture, their response to loading changes accordingly, with dilation at larger strains leading to an increase in strength. The frictional strength of two of these soils, a high-plasticity clay from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…With regard to the parameters obtained from the oedometric tests, the C c soil values in this study (0.06-0.36) are similar to those determined by Hürlimann et al [14] for the volcanic soils of Tenerife (Spain), where the value for this index was 0.287. Conversely, the C c value range of this survey is similar to the C c value of 0.22 obtained for volcanic soils identified as medium-plasticity red silt (ML) from Kapolei, Hawaii (USA), and much less than the C c value of 0.49 for the high-plasticity brown clay (CH) in this same zone obtained by Brandes and Nakayama [13].…”
Section: Discussion Of the Geotechnical Characterization Studysupporting
confidence: 81%
See 2 more Smart Citations
“…With regard to the parameters obtained from the oedometric tests, the C c soil values in this study (0.06-0.36) are similar to those determined by Hürlimann et al [14] for the volcanic soils of Tenerife (Spain), where the value for this index was 0.287. Conversely, the C c value range of this survey is similar to the C c value of 0.22 obtained for volcanic soils identified as medium-plasticity red silt (ML) from Kapolei, Hawaii (USA), and much less than the C c value of 0.49 for the high-plasticity brown clay (CH) in this same zone obtained by Brandes and Nakayama [13].…”
Section: Discussion Of the Geotechnical Characterization Studysupporting
confidence: 81%
“…This study's soil classification is consistent with the volcanic soil classifications of other researchers, as is the case with Hürlimann et al [14], who worked with soils in Tenerife, Canary Islands (Spain), and mainly identified them as silty sands (SM); Crosta et al [10], who investigated the volcanic soils of the Santa Tecla (El Salvador) zone and recognized the presence of low to high-plasticity silts (ML and MH), medium-plasticity clays (CL), and silty sands (SM); and Brandes and Nakayama [13], who studied the volcanic soils in the islands of Oahu and Hawaii (USA), which were identified as medium-to-high plasticity silts (ML and MH) and high-plasticity clays (CH) and silty sands (SM).…”
Section: Discussion Of the Geotechnical Characterization Studymentioning
confidence: 98%
See 1 more Smart Citation
“…In the primary and secondary stages of creep, soil materials are in a stable condition, but they may collapse when reaching the tertiary stage of creep. Many extensive laboratory investigations have been conducted with triaxial apparatus and oedometers to examine the creep behavior of various kinds of soils [ 18 , 19 , 20 ], but almost all of them focus only on the pre-peak-state creep behavior of soil materials. Numerous theories, equations and models have been proposed to account for the creep behavior of clayey soils [ 21 , 22 , 23 ] and various geotechnical issues [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some research has been completed on the weathering of basalts in Fiji (Bonato and Morrison, 2012;Morrison et al, 1986Naidu et al, 1987), but few studies have looked comprehensively at the parent material chemistry, mineral transformations during weathering, and the resulting soil chemistry. There has also been ongoing interest in 'laterisation' (Brandes and Nakayama, 2010;Ollier, 1994;Schellmann, 1981), as this has been observed frequently in parts of the Fiji Archipelago, particularly associated with pedological studies, and the bauxite and manganese mining operations of the 1940s and 1950s (Colley, 1976;Morrison et al, 1987;Twyford and Wright, 1965). This study was initiated to examine the weathering products of the Nasinu Basalt, a relatively extensive area of basalt flows in south-east Viti Levu, the main island of the Fiji group to see if laterisation is occurring.…”
Section: Introductionmentioning
confidence: 99%